Replication Fork Reversal and Protection - Qiu, Shan; Jiang, Guixing; Cao, Liping; Huang, Jun (Frontiers in Cell and Developmental Biology, 2021)
During genome replication, replication forks often encounter obstacles that impede their progression. Arrested forks are unstable structures that can give rise to collapse and rearrange if they are not properly processed and restarted. Replication fork reversal is a critical protective mechanism in higher eukaryotic cells in response to replication stress, in which forks reverse their direction to form a Holliday junction-like structure. The reversed replication forks are protected from nuclease degradation by DNA damage repair proteins, such as BRCA1, BRCA2 and RAD51. Some of these molecules work cooperatively, while others have unique functions. Once the stress is resolved, the replication forks can restart with the help of enzymes, including human RECQ1 helicase, but restart will not be considered here. Here, we review research on the key factors and mechanisms required for the remodeling and protection of stalled replication forks in mammalian cells.